Non-Repudiation In Web Services. - Ling, Elvis,Ing Seng; Khoo, Vincent (2007)
A web service is a set-of-.programmable functions that could be invoked protocols, and consumed through some internet The design of Web services has been plagued with security flaws. Web services invocations could be executed on the fly with the invokers remain anonymous.